The range and extent of the Vallesian Crisis (Late Miocene): new prospects based on the micromammal record from the Vallès-Penedès basin (Catalonia, Spain) - Casanovas-Vilar, I.; van den Hoek Ostende, L.W.; Furió, M.; Madern, P. A. (Journal of Iberian Geology, 2014)
The Vallesian Crisis was initially recognized as a local event, which implied the extinction of certain rodent and artiodactyl genera coincidingwith the early/late Vallesian boundary (at 9.7 Ma). Following works increased the range and extent of this event to encompass allEurope and involve a great number of mammal taxa. Here, we analyze the Vallesian rodent and insectivore record of the Vallès-Penedèsbasin (Catalonia, Spain), where the crisis was first recognized. We show that the quality of the record before the crisis is comparativelymuch better than afterwards so diversity appears inflated and extinction rates are overrated. Accordingly, we used inferred taxon rangesand rarefaction to calculate new diversity measures independent of sample size. These measures virtually eliminate the Vallesian Crisis,showing that diversity somewhat decreased during the earliest late Vallesian and soon recovered afterwards. This is because it cannot bediscarded that several rare taxa, customarily said to have disappeared during the crisis, are in fact present. Amongst the rodents and insectivores,these taxa include genera that are generally rare and show a discontinuous record during the early Vallesian. These are presumedspecialists adapted to humid forested environments such as flying squirrels, beavers or certain dormice, most of them being only recordedwhen the sample size is large enough. Alternatively, these genera may have been associated to very specific habitats which, for an unknownreason, are not sampled during the late Vallesian. Our results cast serious doubts on the very existence of the Vallesian Crisis suggesting thatrather than an abrupt event a series of extinctions occurred during a longer time span. It has not been evaluated whether the same patternis observed in the case of large mammals and in other areas. However, our results show that biases introduced by the quality of the recordneed to be taken into account when assessing the extent of the event.